2011
DOI: 10.1371/journal.pone.0019825
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Influenza Activity of Marchantins, Macrocyclic Bisbibenzyls Contained in Liverworts

Abstract: The H1N1 influenza A virus of swine-origin caused pandemics throughout the world in 2009 and the highly pathogenic H5N1 avian influenza virus has also caused epidemics in Southeast Asia in recent years. The threat of influenza A thus remains a serious global health issue and novel drugs that target these viruses are highly desirable. Influenza A possesses an endonuclease within its RNA polymerase which comprises PA, PB1 and PB2 subunits. To identify potential new anti-influenza compounds in our current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 40 publications
0
94
1
Order By: Relevance
“…Endonuclease inhibition assay. Endonuclease activity assays were performed as described previously (33,34,42,50). Briefly, the 209-residue N-terminal domain of the influenza A virus PA protein (PA N ) was cloned and His tag purified (42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endonuclease inhibition assay. Endonuclease activity assays were performed as described previously (33,34,42,50). Briefly, the 209-residue N-terminal domain of the influenza A virus PA protein (PA N ) was cloned and His tag purified (42).…”
Section: Methodsmentioning
confidence: 99%
“…PA endonuclease inhibitors, including the 4-substituted 2,4-dioxobutanoic acid derivatives (29,30) and the substituted 2,6-diketopiperazine natural product flutimide (31,32), were characterized 2 decades ago in enzymatic, cell-based, and limited in vivo assays (29), where they demonstrated potent (micromolar 50% inhibitory concentrations [IC 50 s]) and cap-dependent inhibition of influenza A and B viruses. Subsequently, marchantins, catechins (33,34), hydroxamic acid and N-hydroxyimides (35,36), 3-hydroxypyridin-2(1H)-one derivatives (37, 38), 3-hydroxyquinolin-2(1H)-one derivatives (39), fullerene derivatives (40), and carboxamide derivatives (41) were identified as PA protein inhibitors. In many of these studies, a library of compound derivatives was screened with a limited number of influenza viruses and/or assays, making it difficult to compare the reported efficacies accurately (42).…”
mentioning
confidence: 99%
“…Another endonuclease inhibitor identified by these investigators is flutimide, a fully substituted 1-hydroxy-3H-pyrazine-2,6-dione isolated from a fungus (21), which served as a lead compound for developing a series of more potent aromatic analogues (22). These discoveries were soon followed by others, resulting in a chemical variety of reported influenza virus endonuclease inhibitors, e.g., N-hydroxamic acid and N-hydroxyimide compounds (23), tetramic acid series and diketobutanoates (24), polyphenolic catechins (25), phenethylphenylphthalimide analogs derived from thalidomide (26), macrocyclic bisbibenzyls (27), a group of compounds bearing distinct pharmacophoric fragments (28), and 3-hydroxyquinolin-2(1H)-ones (29). An effort was also made to define the essential pharmacophore from the available structure-activity relationship (24).…”
mentioning
confidence: 99%
“…The recombinant PA endonuclease activity of the influenza A virus was determined following previously described methods (13)(14)(15)(16), with modifications. The assay was performed in a 100 µL reaction mixture containing 20 mM Tris-HCl (pH 7.3), 100 mM NaCl, 2.5 mM MnCl 2 , 10-50 µg/mL circular single-stranded DNA (M13mp18) as a substrate, and 5 μM recombinant PA endonuclease.…”
Section: Pa Endonuclease Inhibition Assaymentioning
confidence: 99%
“…This suggests that the PA N-terminal endonuclease is a promising therapeutic target for influenza. Our previous results showed that catechins, phenethyl phenyl phthalimide analogs, marchantins, and fullerene C 60 analogs inhibit PA endonuclease activity (in the influenza A virus H1N1 strain) and possess antiviral activity against influenza viruses A (H1N1 and/or H3N2) and/or B strains (13)(14)(15)(16) (17,18). Recently, a Kampo medicine, maoto, was reported to have anti-influenza activity (18).…”
Section: Introductionmentioning
confidence: 99%